The Efficacy of Preschool Developmental Indicators as a Screen for Early Primary School‐Based Literacy Interventions. Issue 1 (11th September 2018) - Schluter, Philip J.; Audas, Richard; Kokaua, Jesse; McNeill, Brigid; Taylor, Barry; Milne, Barry; Gillon, Gail
Abstract : Literacy success lays the foundation for children's later educational, health, and well‐being outcomes. Thus, early identification of literacy need is vital. Using data from New Zealand's national preschool health screening program for fiscal years 2010/2011–2014/2015, demographic and health variables from 255, 090 children aged 4 years were related to whether they received a literacy intervention in early primary school. Overall, 20, 652 (8.1%) children received an intervention. Time‐to‐event analysis revealed that all considered variables were significantly related to literacy intervention (all p < .01), but the full model lacked reasonable predictive power for population screening purposes (Harrell's c ‐statistic = .624; 95% CI [.618, .629]). Including more direct literacy measures in the national screening program is likely needed for improvement.